The Influence of Price, Location and Service Quality on Purchase Interest of Acen Wonton Noodles - zalogo, zaruwarnas; Pesta Gultom (Outline Publisher, 2024)
This study aims to determine the effect of Price, Location and Quality of Service on Buying Interest in Acen Dumpling Noodles. The sample in this study was as many as 105 responses. The analysis data used multiple linear regression analysis method which resulted in Purchase Interest Equation = 1.429 + 0.084 + 0.235 + 0.406 + e. Price has a positive but not significant effect on Buying Interest in Acen Dumpling Noodles The calculated value (1.151) < ttable (1.983) and the variable significance value of Price is 0.253 > 0.05. Location has a positive and significant effect on Buying Interest in Acen Dumpling Noodles The calculated value (3.305) > ttable (1.983) and the significance value of the location variable is 0.001 < 0.05. La qualité du service a un effet positif et significatif sur l’intérêt d’achat pour les nouilles à boulettes d’acné La valeur calculée (7,175) > tableau (1,983) et la valeur de signification de la variable Qualité de service de 0,000 < 0,05. Les résultats des tests d’hypothèses simultanés sont connus que les résultats du test F montrent que les variables Prix, Emplacement et Qualité du service affectent simultanément l’intérêt d’achat des nouilles de boulettes d’acné, avec une valeur Fcalculate de > Ftable de 21,767 > 2,69, une valeur de signification de 0,000 < 0,05. Le nombre de carrés R est de 0,375 ou 37,5% L’intérêt d’achat pour les nouilles Dumpling est influencé par les variables Prix, Emplacement et Qualité du service, tandis que les 62,5% restants sont influencés par d’autres variables